Shifting Wage Norms and Their Implications - Perry, George L. W. (American Economic Review, 1986)
At least since the early 1970's, it has been apparent that the cyclical variations in inflation summarized by the short-run Phillips curve are only one part of the inflation problem that confronts modern industrial economies. Another part is the relative persistence of an established rate of inflation. There is a good deal that we do not understand about this persistence. But I find the most useful way to model it is to start with the concept of a relatively stable wage norm, by which I mean a norm for the rate of wage increase. The model distinguishes sharply between the cycle and the trend in inflation, with the wage norm determining the trend. The variations in inflation of the typical business cycle take place around the existing wage norm and generate the empirical short-run Phillips curve. The wage norm itself is affected little if at all by the typical business cycle. Historically the wage norm has been shifted by prolonged departures from typical business cycles or by other extreme economic developments. Figuring out more precisely what it takes to shift wage norms, or what might keep them from shifting, is a central challenge for understanding inflation better. Before turning to its implications, let me sketch the behavioral underpinnings of the wage norm model and the empirical evidence about wage norms. The norm rate of wage increase has no allocational significance and describes the trend of nominal wages independent of real aggregate demand or relative demand effects. In this respect, it is like the anticipated rate of inflation in many familiar models. Wages are not determined in an auction-like labor market that clears over any reasonable interval of time. Rather they are established by wage-setting firms with a profit-maximizing interest in their long-run relation with their employees, in some cases in a bargaining situation with unions. Under both the implicit and explicit contracts that thus dominate wage setting, keeping up with the norm is the neutral standard for firms. An individual firm that raises wages in line with the norm neither improves nor worsens its relative position as an employer. A firm that wants to expand employment will, typically, offer a higher wage than would be required just to keep up with the norm. Relative wages and relative employment levels are thus codetermined in this process. When most firms want to expand employment, as in a cyclical upturn, the same behavior is part of the process producing the modest cyclical rise in inflation that we observe as the short-run Phillips curve. Thus the onset of cyclical inflation is not a sign that capital and labor resources are being overutilized. Nor is it a sign that inflation is on an accelerating path or even that wage norms are shifting up. In analyzing U.S. postwar data, I have found the wage norm shifted up substantially by the end of the 1960's and down again, though not by as much, by the end of the 1980-82 recession (see my 1983 paper). The first episode was a period with a historic expansion that ended with several years of very low unemployment rates. The second was a recession of unusual length and severity that ended with the highest unemployment rates since the 1930's. There is also evidence of a small shift down in the wage norm after the weak economic performance of 1957-61, which featured two recessions with only an aborted recovery in between. I also found evidence for Germany, the United Kingdom, and Japan of upward shifts in wage norms in manufacturing industries after the 1960's and downward shifts in the early 1980's (see my 1986 paper). All these episodes suggest the kinds of extreme cyclical developments that have shifted wage norms in the postwar period. *The Brookings Institution, 1775 Massachusetts Avenue, NW, Washington, D.C. 20036. In preparing this paper, I benefited from discussions with Charles Schnl t7.e